The ‘ring of fire’ phenomenon in chronic wounds: A new insight using fluorescence imaging (International Journal of Tissue Repair, 2025)
Aim: To describe the ‘ring of fire’ phenomenon observed during fluorescence imaging of chronic wounds.Methods: The Fluorescence Imaging Assessment and Guidance (FLAAG) trial evaluated 350 patients with a variety of chronic wounds. During the FLAAG trial, the investigators observed a phenomenon when wounds were imaged using the MolecuLight i:X imaging device: bacteria fluorescence aggregated at the margin of the wound. This was most pronounced in diabetic foot ulcers. The term ‘ring of fire’ was coined to describe this clinical observation.Results: Six representative patients taken from the FLAAG trial are presented to demonstrate the ‘ring of fire’ in a variety of wound types. This included three diabetic foot ulcers, two venous leg ulcers and a surgical site infection following lumbar back surgery.Conclusion: This is the first clinical report of this phenomenon. It highlights the importance of focusing on the wound edge when managing nonhealing wounds.